Impact of Altered Gastrocnemius Morphometrics and Fascicle Behavior on Walking Patterns in Children With Spastic Cerebral Palsy - Hösl, Matthias; Kruse, Annika; Tilp, Markus; Svehlik, Martin; Böhm, Harald; Zehentbauer, Antonia; Arampatzis, Adamantios (Frontiers in Physiology, 2020)
Spastic Cerebral Palsy (SCP) affects neural control, deteriorates muscle morphometrics and progressively impairs ambulation. Upon passive testing, gastrocnemius medialis (GM) muscle bellies or fascicles are typically shorter, thinner and less extensible. Relationships between muscle and gait parameters might help to understand gait pathology and pathogenesis of spastic muscles. The current aim was to link resting and dynamic gastrocnemius medialis (GM) morphometrics and contractile fascicle behavior (both excursion and velocity) during walking to determinants of gait. We correlated gait variables and ultrasonography of the GM muscle belly captured during rest and during gait in children with SCP (n=15, GMFCS level I and II, age: 7-16y) and age-matched healthy peers (n=17). The SCP children’s plantarflexors were -28% weaker. They walked 13% slower with more knee flexion, 7/15 landed on their fore-foot and produced -42.5% less peak ankle push-off power (all p<0.05). During stance phase, fascicles in SCP operated on 10% shorter length (p=0.04) (normalized to rest length), and displayed less and slower fascicle shortening (-37% and -30.6%, respectively) during push-off (all p<0.01). Correlation analyses in SCP patients revealed that 1) longer resting fascicles and thicker muscle bellies positively relate to faster walking and to less flexed knees (r=0.60-0.69, P<0.017) but not to better ankle kinematics; 2) reduced muscle strength was associated with the extent of eccentric fascicle excursion (r=-0.57, p=0.015) and 3) a shorter operating length of the fascicles was related with a better push-off power (r=-0.58, p=0.013). Only in controls, a correlation (r=0.61, p=0.0054) between slower fascicle shortening velocity and larger push-off power was found. Speculatively, a shorter relative fascicle length in SCP might compensate longer sarcomere lengths which would shift the operating region to produce more force during push-off. Inducing GM atrophy in SCP may correct equinus during gait but promotes knee flexion, so the usually seen vertical collapse during maturation is probably prevented by preservation of muscle size. This raises concerns about invasive treatments. Results emphasize strengthening to limit eccentric overloading which may promote a cascade muscle wasting.